Sistem Informasi Keuangan Pada Koperasi Karya Utama Mandiri - Sugiartawan, Putu; Suryawan, I Gede Totok; Indawan, I Gusti Agung (INFOTEKS (Information Technology, Computer and Sciences), 2022)
In the advancement and use of technology, information systems are very important in an institution or agency as an easily accessible work tool. An information system is a formal, sociotechnical and organizational system designed and used as a means for storing, accessing and distributing information. Several studies have analyzed the design of information systems for sharia cooperatives outside the island of Bali, by developing a financial system based on customer data in the city of Madiun. This research is devoted to the Karya Utama Mandiri Cooperative located in Sanggulan BTN Housing, Tabanan, Bali, established in 2005. Currently, cooperative operations are still carried out manually using Excel, which is prone to errors and data loss. The research methods used include interviews, observation, literature recall, and documentation. The result of this research is the development of a website-based information system with important features, such as Customer Master Data Input, Credit Application Validation, Deposit Master Data, Loan Master Data, Outgoing and Incoming Cash Transactions, Cash Adjustment Transactions, Marketing Master Data, Employee Master Data , and KAS Report Data. The implementation of this financial information system at the Karya Utama Mandiri Cooperative has succeeded in facilitating transaction processes, data processing, reporting, and reducing data damage caused by software.